2015
DOI: 10.3329/sja.v12i2.21927
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Morphometric characterization of indigenous chickens at Jhenaigati upazila of Sherpur district in Bangladesh

Abstract: The study was conducted at Rangtia, Shalchura and Dudhnoi villages under Jhenigati upazilla of Sherpur district in Bangladesh for phenotypic and morphometric characterization of indigenous chickens. Among three types of indigenous chickens, Non-descript Deshi were prominent (86%), compared to Cap Headed (10%) and Naked Neck (4%) and the overall mean body weight, back length, body circumference and pelvis width were 961.50 ± 17.79 gm, 152.70 ± 1.29 mm, 219.20 ± 1.89 mm and 25.57 ± .62 mm respectively. The promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
5
7
1
1
Order By: Relevance
“…Further the results showed that availability of plans and usage of resources had no correlation with timeliness of activity delivery with r=0.024 and r=0.077 respectively. These results revealed that plans were not availed on time and resources were not timely used which could have influenced the performance of indigenous chicken projects.This result is in agreement with the study of Tabassum, et al, (2014) and Sathe (2012) where they indicated that lack of timely availability of resources influences performance of indigenous chicken projects.…”
Section: Indicatorssupporting
confidence: 92%
See 2 more Smart Citations
“…Further the results showed that availability of plans and usage of resources had no correlation with timeliness of activity delivery with r=0.024 and r=0.077 respectively. These results revealed that plans were not availed on time and resources were not timely used which could have influenced the performance of indigenous chicken projects.This result is in agreement with the study of Tabassum, et al, (2014) and Sathe (2012) where they indicated that lack of timely availability of resources influences performance of indigenous chicken projects.…”
Section: Indicatorssupporting
confidence: 92%
“…This result revealed that the performance of indigenous chicken improved as most project implementers used brooders to brood their chicks and fed them with chick mash. Similarly on timely activity delivery, the project implementers agreed that they got the plan of activities early, formed groups which facilitatedearly trainings with a mean score of 3.7971 and acquired their chick brooders earlywith mean score of 3.7029 as asserted by Tabassum, et al, (2014) where they indicated that the resources should be timely acquired. This result revealed that the project management was delivered on time; the project implementers undertook the management practices on time hence improving performance of indigenous chicken.…”
Section: Performance Of Indigenous Chicken Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Alabi et al (2012), body weight was highly correlated with linear body measurements in Naked Neck and Venda chickens and it was non-significant (p> 0.01) in Koekoek chicken of South Africa. In another study, Tabassum et al (2014) also reported that the highest correlation (0.70) between body weight and body circumference, followed by correlation (0.36) between body weight and back length, and correlation (0.27) between body weight and pelvis width were observed. But there was no significant correlation between back length and body circumference, back length and pelvis width, and body circumference and pelvis width.…”
Section: Correlation Among Quantitative Traitsmentioning
confidence: 79%
“…neck plumage color was strongly associated with back plumage color, while wing plumage color was associated with neck and back plumage colors. Whereas, Tabassum et al (2014) reported that bird and comb type, shank, eggshell, earlobe, skin and plumage color had no significant correlation between each other. So bird type, plumage color, shank color or eggshell color did not affect each other significantly of indigenous chickens at Jhenigati Upazilla of Sherpur district in Bangladesh.…”
Section: Correlation Among Qualitative Traitsmentioning
confidence: 93%